Oral and dental health utilization determinants in special health care needs: a systematic review of reviews - Zahra Zare; Mohammad Amin Bahrami; Peivand Bastani; Zahra Kavosi (BMC, 2024)
Abstract Background Oral health is essential for overall well-being and can significantly improve quality of life. However, people with special health care needs (SHCN) often face challenges in accessing dental services. This study aimed to systematically review all available evidence on the oral and dental service utilization determinants among these individuals. Based on the findings, we also explore strategies to increase their access to dental care. Method This study is a systematic review of reviews based on the PRISMA 2020. Six databases were systematically searched including PubMed, Web of Science, Scopus, Embase, ProQuest, and Cochrane Library. Related keywords were applied up to 30 October 2023. This study includes all systematic, scoping, and rapid reviews written in English that examine the factors affecting dental service use among SHCNs. Microsoft Power BI was used for descriptive quantitative analysis, and MAXQDA version 10 was applied for qualitative thematic analysis. Results The number of 2238 articles were retrieved based on the search strategy. After excluding duplications and appraising the eligibility, 7 articles were included. An examination of these 7 articles shows that they were all carried out from 2016 to 2022. Of these, 42% were systematic reviews, 42% used a scoping method, and one study (14%) was a rapid review. According to the thematic analysis, there were five main themes concerning determinants of oral and dental utilization of SHCN: "Financial considerations," "Patient-Provider Relationship," "Accessibility and Availability of Services," "Patient Factors," and "Quality of Care." Additionally, regarding strategies for improving utilization, three main themes emerged: "Education and Training," "Service Improvement," and "Policy Solutions. Conclusion This study delves into the intricate challenges SHCNs face in accessing dental services, highlighting the imperative for comprehensive interventions addressing supply and demand. Supply-oriented measures encompass dentist education, implementing financial policies for affordable services, and integrating dental care into primary healthcare systems. On the demand side, strategies revolve around empowering patients and caregivers and enhancing cultural inclusivity. Despite sustained efforts, current utilization rates fall short of optimal levels. Thus, effective strategic planning by policymakers and healthcare leaders is paramount to bolster dental service utilization among SHCNs, thereby enhancing their overall well-being.